The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1161/01.cir.101.9.1060
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Sympathetic Innervation Influences Local Myocardial Repolarization in Normally Perfused Rabbit Hearts

Abstract: Background-Heterogeneity of sympathetic innervation is thought to contribute to the potential for fatal arrhythmia.However, little is known about the effects of heterogeneous innervation on repolarization. Methods and Results-To assess this relationship, we measured activation recovery intervals (ARIs) from 64 epicardial sites in 11 rabbits studied 2 weeks after regional denervation produced by phenol and 4 sham-operated rabbits. ARI results were compared with the distribution of sympathetic innervation measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…Interestingly, they show evidence of norepinephrine depletion on histologic and histofluorescent catecholamine analysis, although they appear to be histologically normal. These studies were confirmed by Yoshioka et al 34 in rabbits with regional denervation due to application of phenol. Activation recovery interval (ARI), a surrogate of ERP, was used in these studies to show that norepinephrine infusion shortened ARI in 98% of denervated regions, with increase in both shortening and dispersion of ARI in more severely denervated regions.…”
Section: Myocardial Infarction Heart Failure and Sympathetic Innervsupporting
confidence: 61%
“…Interestingly, they show evidence of norepinephrine depletion on histologic and histofluorescent catecholamine analysis, although they appear to be histologically normal. These studies were confirmed by Yoshioka et al 34 in rabbits with regional denervation due to application of phenol. Activation recovery interval (ARI), a surrogate of ERP, was used in these studies to show that norepinephrine infusion shortened ARI in 98% of denervated regions, with increase in both shortening and dispersion of ARI in more severely denervated regions.…”
Section: Myocardial Infarction Heart Failure and Sympathetic Innervsupporting
confidence: 61%
“…Heterogeneous intramyocardial sympathetic nerve sprouting at scar border zones leads to labile repolarization, increased peak Ca 2ϩ current, and susceptibility to ventricular fibrillation in hypercholesterolemic rabbits (15). Increased transmural dispersion of repolarization has also been reported (13,28), along with alterations in transient outward and inward rectifier K ϩ currents (21) in a postinfarct model with nerve sprouts.…”
mentioning
confidence: 96%
“…RT extends from the start of the QRS wave to the maximum differential of the T wave (ie, sum of AT and ARI) and it was used as an index of the time from the depolarization to repolarization. 10 All of the measurements were made in 3 consecutive heartbeats during sinus rhythm, and the mean values were calculated. ARID was calculated as the difference between the maximal ARI (max-ARI) and the minimum ARI (min-ARI) in the 64 measurement regions, and it was used as an index of the 2-dimensional dispersion on the heart's surface.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Antzelevitch et al have reported on the effect of class III drugs on the TDR in wedge models in normal dogs. 10,19,20 Sicouri et al stated that chronic oral administration of AMD in dogs reduced the TDR by causing APD prolongation in the epicardium and endocardium of the LV, and APD shortening in M cells. 19 On the other hand, when they administered IKr blockers, such as E-4031, and d-sotalol, there was a relative increase in the TDR as a result of preferential APD prolongation in the M cells.…”
Section: Effect Of Class III Anti-arrhythmia Agents On Tdr In the Lv mentioning
confidence: 99%
See 1 more Smart Citation